"What choice do you have knowing your child can't breathe?!": Adaptation to Parenthood for Children Who Have Received a Tracheostomy - Ellinor Rydhamn Ledin RN, MSc; Andrea Eriksson PhD; Janet Mattsson RN, MD (SAGE Publishing, 2024)
Introduction A growing number of parents are navigating parenthood influenced by medical complexity and technological dependency as the group of children with long-term tracheostomy grows. However, little is known regarding the parental experiences of parenthood for this heterogeneous group of children now surviving through infancy and intensive care. Objective This study aimed to analyze how parents of children who have received a tracheostomy adapted to parenthood. Methods Interviews were conducted and analyzed following a constructivist grounded theory approach. Ten parents of seven children living with a tracheostomy in Sweden were recruited via the long-term intensive care unit (ICU). Results The core variable of parenthood "Stuck in survival" was explained by two categories and six subcategories. The category "Unaddressed previous history" describes the experiences from being in the ICU environment and how the parents are not able, due to insufficient time and resources, to address these stressful experiences. The category "Falling through the cracks of a rigid system" describes how the parents found themselves and their children to be continuously ill-fitted in a medical system impossible to adapt to their needs and situation. Parents placed the starting point of parenthood with the birth of the child, whilst the tracheotomy only constituted a turning point and would lead to the loss of any previously held expectations regarding parenthood. Conclusion This study identified a previously undescribed period prior to tracheostomy placement, which may have long-lasting effects on these families. The care provided in ICUs following the birth of a child who will require tracheostomy may not be tailored or adapted to accommodate the needs of these families leading to long-lasting effects on parenthood.